Food preferences of Tarnów primary school children in the context of the occurrence of obesity - Kołpa, Małgorzata; Grochowska, Aneta; Brończyk, Wojciech; Kaniewska, Monika (Health Promotion & Physical Activity, 2016)
Introduction: The problem of obesity concerns not only adults but also children and teenagers. It is one of the most frequent developmental disorders among children. Around 20% of children have excessive body mass, and one-third of this group are obese children. The aim of the study was the assessment of the occurrence of obesity among 5th-6th graders of primary school and check children’s knowledge about proper nutrition principles. Material and methods: The method of diagnostic survey was used a questionnaire addressed to children. The questions concerned the child’s diet and checked the knowledge about healthy diet. In the course of the research anthropometric measurements were taken, the Body Mass Index (BMI), as well as Cole index were calculated. The survey was conducted from 1 September to 30 October 2014, among 400 children attending the 5th and 6th grade, in 8 primary schools in Tarnów. Results: As a result of the analysis it was found out that boys in comparison with girls statistically significantly more frequently ate vegetables once a week (p<0.001). Children’s diet influences their physical development, including body mass. The biggest observed body mass was 93 cm, and the smallest was 23.7 kg. The maximum difference between the body mass of individual children was 69.3 kg. The biggest value of BMI was 39.21, whereas the lowest BMI was 13.06. Conclusions: The level of knowledge about healthy lifestyle among the surveyed children is not sufficient to keep the proper body mass. The respondents most often snack sweets, cakes, crisps and sweet fizzy drinks between meals. The mentioned product should be replaced by vegetables, fruit and natural juices.